2013
DOI: 10.1097/01.naj.0000437112.43059.a0
|View full text |Cite
|
Sign up to set email alerts
|

Routine Dyspnea Assessment on Unit Admission

Abstract: OVERVIEW Dyspnea assessment is valuable in diagnosis, prognosis, symptom management, and targeted intervention, and in the allotment and management of patient care resources. The assessment of dyspnea, like that of pain, depends on patient self-report. Expert consensus panels have called for dyspnea to be measured quantitatively and documented on a routine basis, as is the practice with pain. But little information is available on how to measure and record dyspnea ratings systematically. Consequently, the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…Efforts are being made to improve the methods used to measure dyspnoea and determine the ideal frequency of measurement. 23 Dyspnoea is becoming recognised as a 'vital symptom' that impacts on patient outcomes.…”
Section: Dyspnea: the First Vital Sign Prof Bob Banzettmentioning
confidence: 99%
“…Efforts are being made to improve the methods used to measure dyspnoea and determine the ideal frequency of measurement. 23 Dyspnoea is becoming recognised as a 'vital symptom' that impacts on patient outcomes.…”
Section: Dyspnea: the First Vital Sign Prof Bob Banzettmentioning
confidence: 99%
“…Assim, sabendo que os enfermeiros não dispõem de escalas de avaliação da dispneia no SAPE®, nem recorrem às mesmas para a avaliação da intensidade da dispneia do doente, pode afirmar-se que os enfermeiros diagnosticam corretamente a dispneia em repouso e a dispneia funcional, mesmo sem recurso a uma escala de avaliação específica. Segundo o estudo de Baker et al (2013) Por fim, pode concluir-se que a questão de investigação lançada e os objetivos propostos para este estudo foram respetivamente respondidos e obtidos. Emergem, no entanto, algumas reflexões.…”
Section: Discussionunclassified
“…As vantagens deste processo são várias. Por um lado, uma avaliação quantitativa precoce e frequente da dispneia permite um melhor controlo da mesma, alívio do sofrimento e diminuição da possibilidade de agravamento da doença (Baker et al, 2013). Por outro lado, permite registos de enfermagem (RE) mais fidedignos e relacionados com as queixas do doente e, por conseguinte, possibilita intervenções de enfermagem mais adequadas às necessidades da pessoa.…”
Section: Introductionunclassified
“…A growing body of evidence suggests that routine measurement and documentation of dyspnea would have clinical value disproportionate to the minimal effort needed to obtain the data. Our group has shown that routine nursing measurement of dyspnea in hospitalized patients is feasible, and that it may provide useful risk prediction [25-27] …”
mentioning
confidence: 99%